Human Rights and Social Work as Drivers of Inclusive Policy in Democratic Contexts - Justino, E.; Belchior-Rocha, H.; Casquilho-Martins, I. (Expert Seminar: Access to Social Rights in Democratic Societies, 2025)
Human rights and social work share a common mission: promoting dignity, equality, and justice—principles essential for democratic governance and inclusive policy. The presentation explores the intersection of human rights and social work as drivers of systemic change, emphasizing their foundational role in shaping responsive and equitable policies. Drawing on Garrett’s assertion that human rights are “part of the DNA of social work,” argue that practitioners must move beyond service delivery to embrace political engagement. Conley highlights that fears of neutrality often hinder social workers from engaging politically, yet advocacy and participatory research are critical for democratizing knowledge and amplifying marginalized voices. By positioning communities as co-researchers, participatory approaches challenge traditional power dynamics and foster contextually relevant solutions. However, uncritical human rights discourse risks becoming symbolic rather than transformative. Following Bourdieu’s critique of “moral exhibitionism,” we stress the need for reflexivity to avoid imposing Western-centric models that perpetuate inequality. Incorporating Indigenous and decolonial perspectives ensures that rights-based frameworks respect cultural diversity and historical contexts, as advocated by Moka-Mubelo. This pluralistic approach rejects one-size-fits-all solutions, promoting dialogue and collaboration to adapt universal principles to local realities. Our call to action urges educators to embed human rights and participatory methods into social work curricula, equipping future professionals to engage in ethical advocacy. Policymakers must partner with social workers to design inclusive policies grounded in lived experiences. Together, these efforts transform human rights from aspirational rhetoric into actionable tools for equity and social justice. Ultimately, social work cannot remain apolitical in the face of systemic injustice; political engagement is imperative to strengthen democratic accountability and ensure that vulnerable populations are not left behind.